Case report of hepatic pseudocyst: A rare manifestation of liver metastasis from an anal squamous cell carcinoma. (2019) - Bekki, Tomoaki; Takakura, Yuji; Kochi, Masatoshi; Kushitani, Kei; Mori, Keiichi; Arihiro, Koji; Teraoka, Yoshifumi; Egi, Hiroyuki; Ohdan, Hideki
Highlights: Liver metastasis of anal squamous cell carcinoma with a presented pseudocyst is very rare. Some hepatic diseases such as infections, simple biliary cysts, and neoplasms demonstrate a cystic change of the liver. Metastasis should be suspected when CT findings in patients with a history of gastrointestinal cancer show cystic changes involving the liver. Abstract: Introduction: Liver metastasis of an anal squamous cell carcinoma (SCC) with a pseudocyst is uncommon. There are many diseases which form hepatic cystic lesions and sometimes it is difficult to arrive at an accurate diagnosis. Presentation of case: A 69-year-old woman visited our hospital with complaints of bloody stool and difficult defecation. A palpable mass in the anal canal was found on digital examination. The laboratory tests revealed anemia and raised levels of SCC antigen. On endoscopy a type 2 tumor was identified in the anal canal and biopsy revealed SCC. The patient was diagnosed with advanced anal SCC (cT2N1aM0, cStage IIIA) as a result of the examination and underwent chemoradiotherapy (CRT); unfortunately the tumor persisted after CRT. A salvage abdominoperineal resection with D2 and left lateral lymph node dissection was conducted. Histopathologically, the tumor was diagnosed as poorly differentiated SCC. She was readmitted for fever 3 weeks after surgery, and the abdominal CT showed multiple low density areas with enhancement at the edge of the liver, suggesting abscess or metastasis. The metastatic SCC was revealed by cytology of liver drainage and liver biopsy. Discussion: Anal cancers are sometimes encountered however; a pseudo cystic presentation of a liver metastasis is very rare which makes it difficult to distinguish from other diseases. Conclusion: We present a case of SCC in the anal canal with liver metastasis presenting as a hepatic pseudocyst.